2019
DOI: 10.1177/1077801219857824
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Polyvictimization as Predictors of Intimate Partner Violence in Women From the General Population of Quebec

Abstract: This study aimed to (a) evaluate the prevalence of intimate partner violence (IPV) and revictimization among a representative sample of 1,001 women living in Quebec, Canada; (b) examine whether IPV was predicted by experiences of child maltreatment; and (c) explore the role of polyvictimization on IPV beyond the effect of any type of exposure. Results indicate the prevalence rates of lifetime IPV (10.5%), IPV over the last year (2.5%), and revictimization (7.2%). All forms of child maltreatment predicted an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Second, due to the violent environment in El Salvador, one of the most violent and dangerous areas in Latin America, children tend to be exposed to various types of violence throughout their lives, not only from their parents or guardians, but also from other youths. For instance, gang violence in El Salvador is a serious concern, and the average age for joining gangs is 15 (Cruz et al, 2017). Many girls in El Salvador become victims of sexual violence by gang-affiliated perpetrators, but they do not report this violence due to trust issues with the authorities and worries that their family members might be targets of gang retaliation (Dotson & Frydman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to the violent environment in El Salvador, one of the most violent and dangerous areas in Latin America, children tend to be exposed to various types of violence throughout their lives, not only from their parents or guardians, but also from other youths. For instance, gang violence in El Salvador is a serious concern, and the average age for joining gangs is 15 (Cruz et al, 2017). Many girls in El Salvador become victims of sexual violence by gang-affiliated perpetrators, but they do not report this violence due to trust issues with the authorities and worries that their family members might be targets of gang retaliation (Dotson & Frydman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a time of increased brain growth and a vulnerable stage for social and emotional learning; a strong self-identity, an emotional and physical well-being, and an interest in learning are all regarded as crucial elements for healthy development ( Rode et al, 2019 ). As a result, it can hinder a child’s natural and healthy growth when child maltreatment occurs due to parental intimate partner violence (IPV) ( Brassard et al, 2020 ). Various studies have shown that various developmental consequences might result from adolescents’ exposure to parental IPV ( Alaggia and Donohue, 2018 ; Carlson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unclear if child maltreatment is linked to adult disordered eating independent of IPV and vice versa, or if experiencing both in combination is particularly detrimental. Because people who experience child maltreatment are more likely to experience IPV as adults (Brassard et al, 2020), this is a significant limitation.…”
Section: Introductionmentioning
confidence: 99%
“…IPV is also an emerging risk factor for adult disordered eating (Bartlett et al, 2018; Bundock et al, 2013; Lucea et al, 2012; Wong & Chang, 2016). Even though child maltreatment survivors have an increased risk of experiencing IPV (Brassard et al, 2020), the child maltreatment‐disordered eating and IPV‐disordered eating literatures have developed independently, without explicit attention paid to the overlap of childhood and adulthood victimization. Thus, it is unclear whether the relationship between child maltreatment and adult disordered eating is confounded with adult IPV (or vice versa).…”
Section: Introductionmentioning
confidence: 99%